STATE VIOLENCE AND FAILED LEADERSHIP IN HILARY MANTEL’S WOLF HALL - Mathew, Anjelin; Thakur, Sajal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this paper is to critically analyse the relationship between leadership, violence, and court politics in Mantel’s Wolf Hall, paying particular attention to King Henry VIII’s inability to govern effectively and its ramifications. At its core is Thomas Cromwell, an agent who plots his way through the dangerous world of the Tudor court, teaching viewers the rules of New World interactions. Through exploring issues of manipulation, division, and self-interest as the major concerns of the secondary analysis, this paper reveals that Mantel provided a critique of leadership and its turbulent influence on stability. The study helps fill the gap in research on Mantel’s depiction of leadership as a fragile and selfish enterprise and extends the scholarship on power within history and literature.